Peran Orang Tua Dalam Membagi Waktu Belajar Anak Usia 0-5 Tahun Pada Masa Penggunaan Gadget Di Desa Liprak Kidul - Halim, Abdul; Fitriana, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2023)
Gadgets are sophisticated tools that present various news media, social networks, lifestyle information, hobbies, to entertainment that are presented online and offline, now successfully attracting a lot of public attention. It should be noted that gadgets have positive and negative impacts on humans, especially children. The positive impact for humans is that it is easier to find information, makes learning easier, and also makes work easier. While the negative impact is mental health problems such as anxiety disorders, difficulty focusing and depression, all of which can be caused by gadget addiction. The aims of the researchers in writing this journal are: to get a description of gadgets, to get a description of the function of gadgets and the types of gadgets, to get a description of the positive and negative impacts of using gadgets on children aged 0-5 years, to find out the role of parents in assisting children aged 0-5 years in using gadgets, and finally to get what tips people do in teaching good use of gadgets to children aged 4-6 years.